1998
DOI: 10.1161/01.cir.97.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Serial Changes in Left Ventricular Mass in Essential Hypertension

Abstract: In essential hypertension, a reduction in LV mass during treatment is a favorable prognostic marker that predicts a lesser risk for subsequent cardiovascular morbid events. Such an association is independent of baseline LV mass, baseline clinic and ambulatory BP, and degree of BP reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
327
3
15

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 579 publications
(363 citation statements)
references
References 40 publications
10
327
3
15
Order By: Relevance
“…Various observational studies suggest that LVH reversal is beneficial beyond BP reduction and treatment by demonstrating that CV events occur in higher proportion of individuals in whom LVH progresses than regresses. 19,38 These findings suggest that the level of LV mass during antihypertensive treatment reflects independent information regarding disease progression or its control. Confirmation of this hypothesis comes from two landmark trials; the HOPE and LIFE trials.…”
Section: Ecg Lvh Regression and Prognosismentioning
confidence: 89%
“…Various observational studies suggest that LVH reversal is beneficial beyond BP reduction and treatment by demonstrating that CV events occur in higher proportion of individuals in whom LVH progresses than regresses. 19,38 These findings suggest that the level of LV mass during antihypertensive treatment reflects independent information regarding disease progression or its control. Confirmation of this hypothesis comes from two landmark trials; the HOPE and LIFE trials.…”
Section: Ecg Lvh Regression and Prognosismentioning
confidence: 89%
“…13,14 Reduction in LV mass in turn reduces the repolarization time and its dispersion, [15][16][17] the incidence and severity of ventricular arrhythmias 2 and the risk for cardiovascular events. 18,19 We have recently shown that regression of LV mass induced by the angiotensin II type 1 receptor blocker (ARB) irbesartan rather than by the b 1 -selective adrenoceptor blocker atenolol is accompanied by improved repolarization. 16 There are, however, unsettled questions as to the effects of reverse remodelling by antihypertensive therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The registry was approved by the local ethics committee of the Italian National Health Service and all patients provided their informed consent to participate. Details of the study have been published elsewhere 5, 9, 15. Entry criteria included an office systolic BP ≥140 mm Hg and/or diastolic BP ≥90 mm Hg on at least 3 visits and absence of secondary causes of hypertension, previous cardiovascular disease, or life‐threatening conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Only frames with optimal visualization of interfaces and showing simultaneous visualization of septum, LV internal diameter, and posterior wall were used for reading. Details about reading procedures and reproducibility in our laboratory have been previously reported 5, 9, 18. LVM was calculated by using a necropsy validated formula19 and corrected by height in meters at the power of 2.7 20.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation